(untitled) (Research, Society and Development, 2021)
The purpose of this article is to present an overview of the safety of iron mining dams located in the municipalities of Parauapebas and Canaã dos Carajás, in the southeast of Pará. This study is justified by the recent disasters that occurred due to the rupture of mining dams in the country, emphasizing the need for a more effective safety management of these structures and new methods in mining that reconcile economic and socio-environmental issues. This study involved bibliographic research, analysis of Brazilian dam safety legislation as well as data acquired from official agencies. According to the National Mining Agency (ANM), in the state of Pará there are six iron mining dams in the municipality of Parauapebas, which are part of the National Dam Safety Policy (PNSB), and five dams in Canaã dos Carajás that are not fall under this policy, all of which are the responsibility of Vale S / A. The risk category and the associated potential damage of each structure were analyzed, and if there is a Mining Dam Emergency Action Plan (PAEBM) in the event of an accident. The results indicate that the Gelado, Geladinho and Pera Jusante dams, in Parauapebas, have the greatest potential damage associated, therefore requiring greater control and inspection by the state to ensure the environment and the population that lives downstream from these structures. The safety of the analyzed dams is highly dependent on the monitoring of the responsible company, which, according to the ANM system, has complied with the requirements established by law, such as the preparation of the PAEBM.